Phase equilibria, crystal structure and oxygen nonstoichiometry of the complex oxides in the Sm – (Sr, Ba) – (Co, Fe) – O systems - N. E. Volkova; L. V. Khvostova; A. P. Galaida; L. Ya. Gavrilova; V. A. Cherepanov (Chimica Techno Acta, 2018)
Present paper contains available information on the phase equilibria in the Sm – (Sr, Ba) – (Co, Fe) – O systems, including the synthesis routes used, crystal structure, which is often depended on oxygen nonstoichiometry, the data on thermodynamic stability of complex oxides, the obtained results on the homogeneity ranges of solid solutions, formed in the systems, and graphical presentation of phase relations in a form of phase diagrams.